Testing the Effectiveness of Basil Leaf Essential Oil (Ocimum basilicum L) against Aedes Aegypti Mosquitoes in Aromatherapy Candles - Rahayu, Santi Dwi; Rahmawati, Riana Putri; Arif, Fahrudin (Advances in Healthcare Research, 2025)
Purpose: This study aims to formulate basil leaf essential oil (Ocimum basilicum L.) as an active ingredient against Aedes aegypti mosquitoes in the form of aromatherapy wax that can be applied by inhalation. Research Method: This study is a laboratory experimental study. Essential oil from basil leaves was obtained through steam distillation, while the wax preparation was made using the melting method. The aromatherapy wax formulation consisted of five groups, namely positive control, negative control, formulation I (2%), formulation II (4%), and formulation III (6%). Each formulation was tested through a series of physical property tests, including organoleptic tests (color, odor, and shape), burning time test, melting point test, and effectiveness test as an insect repellent against Aedes aegypti. Data analysis was performed using a one-way ANOVA statistical test and followed by a Tukey Post Hoc test. Results and Discussion: The results showed that aromatherapy candles containing basil essential oil had varying effectiveness against mosquito mortality. Formulations with higher concentrations (4% and 6%) provided the best results in physical testing and biological effectiveness compared to other formulations and controls. Implications: This study supports the development of natural-based aromatherapy candles as a safe, effective, and environmentally friendly alternative insecticide for controlling Aedes aegypti mosquitoes in domestic environments.